Efektifitas Sistem Informasi Manajemen Nikah (SIMKAH) Berbasis Online di Kota Tangerang Selatan - Muhamad Amaral Fiscal; Nida Handayani (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
Public services in the scope of marriage have led to the digitization of public services combined with updating the information systems within them. Online-based public services related to marriage under the name SIMKAH (Marriage Management Information System) are a form of digitalization of public services. The implementation of online-based SIMKAH has generated various responses, especially among the public. This research aims to determine, describe and analyze the effectiveness of the Marriage Management Information System in South Tangerang City. The method used in this research is a descriptive method with a qualitative approach. Data collection techniques using interviews, observation and documentation. The results of research on the indicators for determining the targets for the SIMKAH program are still not precise because it reaches all levels of society. In terms of indicators, the socialization program is not yet optimal because socialization is carried out only when the prospective bride and groom provide administrative documents at the KUA. In terms of program objective indicators, the aim of implementing online-based SIMKAH is not yet fully efficient due to the lack of features that can maintain the operational efficiency of online-based SIMKAH. In terms of monitoring indicators, the SIMKAH program still lacks the execution that should be carried out by the person responsible, in this case collecting information in the form of suggestions and constructive input from the community.